EXTENDED OCCUPATIONAL THERAPY BASED REHABILITATION FOR A YOUNG CLIENT FOLLOWING HEAD INJURY – A CASE REPORT - MRS. KR. BANUMATHE; MR. GURUPRASAD V; DR. KARTHIK RAO N; MR. SURESH SUKUMAR (International Journal of Pharma and Bio Sciences, 2016)
This case study describes an unique long-term functional recovery process toward successful rehabilitation for a young male student with post traumatic head injury. The client was referred to Occupational Therapy (OT) for assessment and management following head injury sequeale. On initial assessment, the client presented with decreased arousal level, cognitive deficits, weakness in the right upper and lower limbs, left sided cerebellar features, difficulty in functional mobility and was dependent for all his daily routine activities. Occupational Therapy intervention focused on strengthening activities, functional balance and mobility retraining, coordination retraining, cognitive rehabilitation, Activities of Daily Living (ADL) retraining, pre academics and leisure skills. The Occupational Therapy sessions lasted for 45 minutes to 1 hour daily. In the initial few sessions more focus was given for sensory stimulation activities. After a month of Occupational Therapy rehabilitation, since the Glasgow Coma Scale (GCS) score improved from 8 to 14, intensive cognitive rehabilitation was provided. Therapy focus was given to the upper extremity strengthening and functional balance retraining. Following 9 months of therapy, the client has shown progress in independent in functional mobility – indoor and outdoor, able to use upper extremity functionally for daily living skills and therapy for higher level cognitive skills and meta-cognitive skills was initiated. The client showed maximum independency in daily living skills and pre-academic skills by the end of 12 months.